Implementasi Islamic Corporate Social Responsibility (ICSR) di Indonesia: Telaah Komprehensif terhadap Tanggung Jawab Sosial Berbasis Syariah - Selvia, Dinda; Albahi, Muhammad; Andrini, Rozi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research is motivated by the phenomenon of the implementation of Islamic Corporate Social Responsibility (ICSR) in Indonesia, which has not yet fully reflected sharia values ​​comprehensively. The purpose of this study is to analyze in-depth the implementation of ICSR in sharia-based companies, identify gaps between normative concepts and empirical practices, and formulate an ideal and sustainable implementation model. The research method uses a qualitative approach with literature analysis and secondary data in the form of sustainability reports and sharia CSR policy documents. The results show that although normatively ICSR is based on the principles of ihsan, tauhid, and maqashid al-syariah as a form of worship and trust, its implementation in the field is still formalistic, administrative, and image-oriented. The findings indicate that ICSR does not significantly impact financial performance, but has a positive impact on reputation and consumer loyalty when implemented substantially and transparently. This study implies the need to revitalize ICSR implementation through the integration of maqashid al-syariah values, the application of the Shariah Impact-Based CSR model, strengthening sharia governance, and impact-based reporting so that ICSR implementation can deliver economic, social, and spiritual sustainability in a balanced manner and in accordance with the objectives of social responsibility in Islam.